Lectures on Mappings of Finite Distortion - Hencl, Stanislav; Koskela, Pekka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
In this book we introduce the class of mappings of finite distortion as a generalization of the class of mappings of bounded distortion. Connections with models of nonlinear elasticity are also discussed. We study continuity properties, behavior of our mappings on null sets, topological properties like openness and discreteness, regularity of the potential inverse mappings and many other aspects.
Introduction -- Continuity -- Openness and discreteness -- Images and preimages of null sets -- Homeomorphisms of finite distortion -- Integrability of Jf and 1/Jf -- Final comments -- Appendix -- References.
Keywords: Mathematics; Global analysis (Mathematics).; Functional analysis; Functions of complex variables; Differential equations, partial; Mathematics; Analysis; Functions of a Complex Variable; Functional Analysis; Partial Differential Equations